Effect of chitosan-thymol ratio on the encapsulation of thymol in chitosan nanoparticle - Ahmad Shapi’i, Ruzanna; Othman, Siti Hajar; Naim, Mohd Nazli; Mohamed Amin Tawakkal, Intan Syafinaz (Elsevier, 2025)
The encapsulated thymol in chitosan nanoparticles (CNP-T) was produced via two-stages ionic emulsion using different chitosan-thymol ratios at 1:0, 1:0.25, 1:0.5, 1:0.75, and 1:1. The characteristics of CNP-T including diameter, stability, loading capacity, chemical interactions, thermal stability, morphology, and antibacterial properties were characterized. The optimum chitosan-thymol ratio that produced the smallest diameter (10 nm) and stable CNP-T was 1:0.5. The encapsulation efficiency and loading capacity of 1:0.5 CNP-T were 57.53 % and 41.52 %, respectively. Fourier-transform infrared spectroscopy (FTIR) spectrum of 1:0.5 CNP-T shows the additional peaks of C-H (2961 and 2872 cm−1) were related to the thymol, verifying the successful encapsulation process. The encapsulated thymol in 1:0.5 CNP-T decomposed at higher temperatures (384.75 ºC) than free thymol (236.27 ºC). It was revealed that CNP-T inhibits the Staphylococcus aureus (S. aureus) and Salmonella typhimurium (S. typhimurium) growth effectively, thus confirming the antibacterial properties of CNP-T. The stable and small size of CNP-T produced in this work are promising for various applications including agriculture, food, and medical industries.